More than meets the eye: understanding Trypanosoma brucei morphology in the tsetse - Ooi, Cher-Pheng; Bastin, Philippe (Frontiers in Cellular and Infection Microbiology, 2013)
T. brucei, the causative parasite for African trypanosomiasis, faces an interesting dilemma in its life cycle. It has to successfully complete its infection cycle in the tsetse vector to be able to infect other vertebrate hosts. T. brucei has to undergo multiple morphological changes as it invades the alimentary canal of the tsetse successively to finally achieve infectivity in the salivary glands. In this review, we attempt to elucidate how these morphological changes are possible for a parasite that has evolved a highly robust cell structure to survive the chemically and physically diverse environments it finds itself in. To achieve this, we juxtaposed the experimental evidence that has been collected from T. brucei forms that are cultured in vitro with the observations that have been carried out on tsetse-infective forms in vivo. Although the accumulated knowledge on T. brucei biology is by no means trivial, several outstanding questions remain for how the parasite mechanistically changes its morphology as it traverses the tsetse and how those changes are triggered. However, we conclude that with recent breakthroughs allowing for the replication of the tsetse-infection process of T. brucei in vitro, these outstanding questions can finally be addressed.